Research on Guqin composition in Mainland China in the 1950s and 1960s: some works of Yu Shaoze [ 喻绍泽] - He, Zeng; Chiat, Loo Fung (Logos Verlag Berlin GmbH, 2024)
After the establishment of the People’s Republic of China in 1949, a group of guqin players from the folk were integrated into official music research and educational institutions. Under the guidance of the cultural policies advocated by the new regime, they created a considerable number of new guqin compositions that reflected the characteristics of the times. This paper primarily focuses on the historical and morphological study of nine guqin pieces composed by Yu Shaoze [ 喻绍泽] (1903–1988), the earliest professional guqin music teacher in the west China, between 1956 and 1966. In the historical research section, the article examines the historical context of these works from two perspectives: the personal circumstances of the guqin player and the socio-political atmosphere in China. In the musicological research section, the article studies these works within the ‘‘author-work’’ relationship to investigate how the guqin player’s performance experience shaped the forms of these compositions. Simultaneously, it explores how the author re-sponded to the political demands and tastes of the Chinese authorities regarding music compositions during the 1950s and 1960s in his creative process.